Pemberdayaan Masyarakat Melalui Pengelolaan Sampah Plastik Menjadi Premium dan Solar Alternatif di Desa Buluagung Kecamatan Siliragung Kabupaten Banyuwangi - Nur Anim Jauhariyah; Nurul Inayah; Mahmudah Mahmudah; M. Alaika Nasrulloh (IAI Darussalam, 2020)
The type of program of activities in this service is Community Empowerment Through Processing Plastic Waste into Premium and Alternative Solar in Buluagung Village, Siliragung District, Banyuwangi Regency, namely to process plastic waste processed into fuel oil by using a plastic catalyst machine as a village innovation, because the BUMDes